The Impact of Economic Growth on Unemployment Case study: The King of Saudi Arabia during the period 1980- 2018 - Hasan, Abbas Fouad Abbas (Journal of Economic, Administrative and Legal Sciences, 2020)
The study seeks to analyze and measure the relationship between rates of unemployment and economic growth in the Kingdom of Saudi Arabia during the period 1980- 2018 and stand on the economic measures by the authorities to address the negative effects of high unemployment rates using the correlation matrix, Granger causality test, the methodology of the Co- integration test, error correction model and Okun model. The study found that there is strong relationship between economic growth and the unemployment rate in the Kingdom of Saudi Arabia during the study period. The study depends on the data from the Saudi Arabian Monetary Agency (SAMA)، the World Bank and other resources. One of the most important hypotheses of the study there is statistically significant relationship between economic growth and unemployment. The study recommended several recommendations one of them is: develop new economic policies to reduce dependence on oil as a primary source of revenue reducing inflation and working to increase investments, which leads to an increase in the size of the labor market.